Estudos teóricos de propriedades eletrônicas e estruturais do PbO e PbO2 - Barretto, Tatiana Conceição Machado [UNESP] (2015)
PbO has two main allotropic phases: a-PbO, massicot type tetragonal structure belonging to space group P42/mnm (129), with cell constants a = 0.3975 nm and c = 0.5022 nm and B-PbO, litharge type orthorhombic structure belonging to the space group Cmma (67), with cell constants a = 0.5609 nm, b = 0.5607 nm and c = 0.4997 nm. PbO2 has two main allotropic phases: a-PbO2, columbite type orthorhombic structure belonging to the space group Pbcn (60), with cell constants a = 0.497 nm, b = 0.596 nm and c = 0.544 nm, and B-PbO2, rutile type tetragonal structure belonging to space group P42/mnm (136), with cell constants a = 0.491 nm and c = 0.3385 nm. a-PbO and B-PbO2 are both considered highly covalent materials with strong hybridization between the 2p orbitals of O and 6s and 6p orbitals of Pb. B-PbO2 is a narrow band gap semiconducting, which has received a great deal of attention lately due to their potential use as TCO. In this work, we adopt a quantum mechanical approach based on the periodic Density Functional Theory (DFT), with B3LYP hybrid potential, to investigate the electronic structure of all phases, aiming to contribute to a better understanding of the materials behavior. The CRYSTAL09 code has been used for the calculations. From the calculations of band structures, it is suggested that the conducting behavior of B-PbO2 is an intrinsic characteristic of the material that arises from the overlaping of the 6s orbital of the conducting band of Pb and the 2p orbital of the top of valence band of O. The charge density of the Pb cations in B-PbO2 and a-PbO2 is about half the formal ionic charge. PbO2 has a small direct band gap